Interaksi antarsuku dalam Kehidupan Sosial Ekonomi Masyarakat Tanjung Luar Lombok Timur - Baiq Nurul Hidayati Safitri; Syahrul Amar; Muhammad Shulhan Hadi; Bambang Eka Saputra; Hanapi Hanapi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This research aims to explain the dynamics and patterns of interaction between tribes in socio-economic life in Tanjung Luar Village, East Lombok. This research method uses qualitative with an ethnographic approach. Data collection techniques include observation, interviews, and documentation. The results of this research show that the pattern of interaction between tribes in the Tanjung Luar area began with the existence of the Baai van Pidjoe port, then around 1907, the port was moved to Tanjung Luar until it was busy being visited by tribes from outside. On the coast of Tanjung Luar, there are several patterns of interaction between tribes in daily life, namely, cooperation, exchange, dispute, and competition. The social impact is the interaction between tribes, a heterogeneous society free of conflict/strengthening unity and integrity, and as a vehicle for inter-tribal meetings. Meanwhile, the impact on the economy is as a means of livelihood or employment, income or ownership of goods, and increased education so that the socio-economic value of society also increases.